Genome-Wide Identification of Loci Associated With Phenology-Related Traits and Their Adaptive Variations in a Highbush Blueberry Collection - Nagasaka, Kyoka; Nishiyama, Soichiro; Fujikawa, Mao; Yamane, Hisayo; Shirasawa, Kenta; Babiker, Ebrahiem; Tao, Ryutaro (Frontiers in Plant Science, 2022)
Genetic variation in phenological traits is key to expanding production areas of crops. Southern highbush blueberry (SHB) is a blueberry cultivar group adapted to warmer climates and has been developed by multiple interspecific hybridizations between elite Northern highbush blueberry (NHB) (Vaccinium corymbosum L.) and low-chill Vaccinium species native to the southern United States. In this study, we employed a collection of diverse SHB accessions and performed a genome-wide association study (GWAS) for five phenology-related traits (chilling requirement, flowering date, ripening date, fruit development period, and continuous flowering) using four GWAS models. Phenology-related traits showed higher heritability and larger correlation coefficients between year replications, which resulted in the detection of robust phenotype-genotype association peaks. Notably, a single association peak for the chilling requirement was detected on Chromosome 4 based on multiple GWAS models. Comparison of genotypes at the GWAS peaks between NHB and SHB revealed the putative introgression of low-chill and late-flowering alleles into the highbush genetic pool. Our results provide basic insights into the diversity of phenological traits in blueberry and the genetic establishment of current highbush cultivar groups.